Halophila beccarii Aschers (Hydrocharitaceae) responses to different salinity gradient - Ismail, Mohd Fakhrulddin; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (Academic Journals, 2013)
Halophila beccarii Aschers., a small monoecious seagrass with rosette leafy shoot and well-developed rhizome or underground stem that acts as anchors occurs in environment with salinity fluctuation e.g., brackish coastal water of mangrove system, lagoon and marine coastal areas. Shoots represent most of the above-ground component of the plant and in direct contact to the ever changing salinity but it is not known how they respond to such fluctuations. Therefore, this study examined the effects of salinity variations on above-ground response variables; number of leaves per shoot, leaf length, leaf width and petiole length of the seagrass Halophila beccarii. Survival and above-ground response variables to salinity were characterized in culture-experiments in which plants were exposed to increased salinity (from 25-30, 45 psu) and decreased salinities (from 25-25, 20, 15, 10, 6, 4, 2, 0.9, 0.52 and 0 psu) treatments at two-week intervals. No plants mortality and significant changes in number of leaves per shoot were observed with increased or decreased salinity treatments. Plants continued to survive even in hypotonic environment to 0 psu. Halophila beccarii was significantly affected by increased or decreased salinity altering the dimensions of leaves. Leaf length and leaf width became shorter and narrower at lower (4-0.52 psu) and higher (45 psu) salinity. These results suggest that the seagrass H. beccarii could be negatively affected by hypo- or hypersalinity conditions, although salinity changes did not alter the tolerance of this species. Halophila beccarii tolerated hyposaline conditions better than hypersaline conditions.